2020
DOI: 10.1155/2020/1309183
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Biodegradation of Four Groups of Steroid Hormones in Activated Sludge

Abstract: Steroid hormones in the environment have obtained considerable attention, as they can be harmful to aquatic organisms at very low concentrations. An analytical method was developed for simultaneously monitoring four estrogens, seven androgens, seven progestogens, and eleven glucocorticoids in a single water sample using liquid chromatography-electrospray tandem mass spectrometry. Laboratory studies were then performed to investigate the aerobic biodegradation of 29 steroids belonging to the four groups. The de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Increasingly, studies have confirmed the presence of DEXA in variant environment matrices, including hospital effluents, industrial effluents, wastewater treatment plants influents and effluents, groundwater, seawater, sediments, soil, surface water, and drinking water across the globe (summarized in Table 2). The presence of DEXA in groundwater, river water, and, eventually, drinking water is attributed to the partial treatment of wastewater from WWTPs [27,[60][61][62]. For example, DEXA has been observed to be inadequately removed in biological activated systems [62].…”
Section: Presence Of Dexa In the Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasingly, studies have confirmed the presence of DEXA in variant environment matrices, including hospital effluents, industrial effluents, wastewater treatment plants influents and effluents, groundwater, seawater, sediments, soil, surface water, and drinking water across the globe (summarized in Table 2). The presence of DEXA in groundwater, river water, and, eventually, drinking water is attributed to the partial treatment of wastewater from WWTPs [27,[60][61][62]. For example, DEXA has been observed to be inadequately removed in biological activated systems [62].…”
Section: Presence Of Dexa In the Environmentmentioning
confidence: 99%
“…The presence of DEXA in groundwater, river water, and, eventually, drinking water is attributed to the partial treatment of wastewater from WWTPs [27,[60][61][62]. For example, DEXA has been observed to be inadequately removed in biological activated systems [62]. This is because WWTPs, by design, treat major organic pollutants in the mg/L range [27,60,63].…”
Section: Presence Of Dexa In the Environmentmentioning
confidence: 99%